COVID-19 and Tourism in Pokhara: Strategies for Industry’s Recovery (Prithvi Journal of Research and Innovation, 2021)
Tourism is considered as travel related activities. Pokhara has many attractions for tourists including lakes, hills, religious and cultural sites. The presence of Phewa Lake in the west, Begnas Lake in the east attracts a large number of domestic and international tourists. The main objective of this study is to explore the impact of COVID-19 on tourism of Pokhara. Altogether 120 samples were taken purposively in the major touristic areas of Pokhara. Interviews were taken with key informants and the observation technique was also used. The obtained data were discussed in the form of table, charts and figures. The number of tourists visiting Pokhara is found decreasing over the last two years due to the Covid-19 pandemic. High quality hotels are only in the Phewa Lake area whereas there are very few quality hotels in the study area, so quality hotels with better facilities should be established in other areas, too. New tourism activities need to be explored and after the operation of international airport, the option for the present paragliding spots need to be managed in time. To minimize the impact of Covid-19 pandemic, there should be a provision of easy refinancing facilities from the financial institutions to be provided to the tourism entrepreneurs, including subsidies on the equated monthly instalments and decreasing the interest rate and quick vaccination to the people involved in tourism sectors.